PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN MUNTAZA TOURS & TRAVEL CIBUBUR. - Gunawan, Ahmad (Universitas Persada Indonesia YAI, 2017)
Motivation and Satisfiction are the two factors of a few relatively large factors suspected to influencePerformance on the Muntaza Tours and Travel Cibubur. These research aimed to determine the effect ofMotivation and Satisfiction toward Performance on Muntaza Tours and Travel Cibubur.Research conducted at the Muntaza Tours and travel by taking 36 employees as the research sample.Data were collected by questionnaire instruments covered by the five rating scale from strongly disagreeto strongly agree. Quantitative research was conducted by describing and analyzing research data. Themultiple linier regression analysis and multiple determination coeficient are the statistic approach to dataanalysis.The study produced three major findings consistent with the hypothesis put forward, that are: 1)Motivation has a significant effect on performance in a positive direction; 2) Satisfiction has a significanteffect on Performance in a positive direction; 3) Motivation and Satisfiction simultaneously influence 94.10%Performance variability. Base on the research finding, in order to increase Performance can be done by increasing Motivationand Satisfiction.